Rates of success in hearing and grafting in the perichondrium-preserved palisade island graft technique - Genç,Selahattin (2021)
Abstract Introduction Various graft materials have been used in the tympanoplasty technique. Cartilage grafts are being used increasingly in recent years. Objective The aim of this study was to present the comparative outcomes of the perichondrium-preserved palisade island graft technique previously defined by ourselves. Methods We retrospectively compared the hearing and graft success rates in 108 patients with chronic otitis media, who had undergone cartilage tympanoplasty, where both island and perichondrium-preserved palisade graft techniques were used. Results The success rates among the study and the control groups with regard to graft take were 97% and 93%, respectively. No significant difference was observed between the groups with regard to the postoperative mean pure tone values, improvement in air-bone gaps and reduction in air-bone gaps to under 20 dB. However, better results were observed in the study group. Conclusion The perichondrium-preserved palisade island graft technique is an easy method with high graft success rates and hearing outcomes.